A new species and two new synonyms from China in the genus Odontothrips (Thysanoptera: Thripidae) - Hu, Qing-Ling; Mirab-Balou, Majid; Chen, Xue-Xin; Feng, Ji-Nian (Zootaxa, 2012)
Odontothrips hani sp. n. is described and illustrated from Fabaceae flowers in China. O. qinlingensis Feng & Zhao and O. yinggeensis Feng & Zhang are newly synonymised with O. loti (Haliday).